SUBALTERNITAS TOKOH DIAH AYU DAN MAHARANI: ANTARA KUTUKAN DAN SENJATA - Irmawati Irmawati; Wahyu Gandi G (Sunan Kalijaga State Islamic University Yogyakarta, 2021)
The story of “Kutukan Dapur” by Eka Kurniawan presents a colonial setting: Dutch colonialism and postcolonialism in the image of two characters, Diah Ayu and Maharani. Maharani is in patriarchal shackles, which is ingrained in her family life and social structure. Meanwhile, Diah Ayu is in the bonds of Dutch colonialism, which is brought back by the author. Both are in a subaltern position but in different conditions. Based on this description, this research asks two questions which are analyzed using Gayatri Spivak's subaltern theory, (1) what the position of Diah Ayu and Maharani in